2020
DOI: 10.1051/0004-6361/202038962
|View full text |Cite
|
Sign up to set email alerts
|

The volumetric star formation law for nearby galaxies

Abstract: In the last decades, much effort has been put into finding the star formation law, which could unequivocally link the gas and the star formation rate (SFR) densities measured on a sub-kiloparsec scale in star-forming galaxies. The conventional approach of using the observed surface densities to infer star formation laws has however revealed a major and well-known issue, as such relations are valid for the high-density regions of galaxies but break down in low-density and HI-dominated environments. Recently, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 121 publications
1
26
0
Order By: Relevance
“…Moreover, the scatter of the rKS has been interpreted as individual star-forming regions undergoing independent evolutionary life cycles (Schruba et al 2010;Feldmann et al 2011), and its dependence on spatial scale provides insight into the timescales of the star formation cycle (Kruijssen & Longmore 2014;Kruijssen et al 2018). Additionally, Bacchini et al (2019aBacchini et al ( , 2020 found a tight correlation between the gas and the SFR volume densities in nearby disk galaxies, suggesting that the scatter of the rKS could be in part related to projection effects caused by the flaring scale height of gas disks. In addition to the rSFMS and the rKS, recently Lin et al (2019), Ellison et al (2021), and Morselli et al (2020) reported the existence of a resolved molecular gas main sequence (rMGMS) as the correlation between the local Σ mol.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scatter of the rKS has been interpreted as individual star-forming regions undergoing independent evolutionary life cycles (Schruba et al 2010;Feldmann et al 2011), and its dependence on spatial scale provides insight into the timescales of the star formation cycle (Kruijssen & Longmore 2014;Kruijssen et al 2018). Additionally, Bacchini et al (2019aBacchini et al ( , 2020 found a tight correlation between the gas and the SFR volume densities in nearby disk galaxies, suggesting that the scatter of the rKS could be in part related to projection effects caused by the flaring scale height of gas disks. In addition to the rSFMS and the rKS, recently Lin et al (2019), Ellison et al (2021), and Morselli et al (2020) reported the existence of a resolved molecular gas main sequence (rMGMS) as the correlation between the local Σ mol.…”
Section: Introductionmentioning
confidence: 99%
“…These values translated into a gas mass densities are typical for other nearby dwarfs and the outskirts of massive galaxies (e.g. Abramova & Zasov 2011;Bacchini et al 2019Bacchini et al , 2020, however the derived values depend on two very uncertain parameters -disc scale height and inclination. In particular, the inclination angle estimates for DDO 53 vary significantly in the literature -from i = 27 • Oh et al (2011) to i = 56 • Boisvert & Rhee (2016).…”
Section: Morphology and Kinematics Of The Atomic Gasmentioning
confidence: 74%
“…As individual and clustered SNe (superbubbles) are likely the most important mechanism for driving turbulence in the ISM (Norman & Ferrara 1996;Ostriker & Shetty 2011;Kim et al 2011;El-Badry et al 2019), the maximum physical scale was limited to the scale of these events. From simulations and theory, the predicted range over which superbubbles input momentum into the ISM is about one to a few times the scale height of the galaxy (Kim et al 2017;Gentry et al 2017), or roughly 200 to 600 pc for dwarf galaxy disk thicknesses (Bacchini et al 2020b). Thus, region sizes larger than 400 pc would not be able to identify the impacts of the local star formation activity from the global star formation activity on the ISM.…”
Section: Galaxy Divisionsmentioning
confidence: 99%